Empirical Study on the Impact of Urban and Rural Resident Basic Medical Insurance on Children's Educational Outcomes - Chen, Hua; Xiao, Gandan; Xing, Jianing; Zhou, Qing (Frontiers in Public Health, 2021)
This paper employs data from the 2016 and 2018 China Family Panel Studies (CFPS) to study the impact of participating in Urban and Rural Resident Basic Medical Insurance (URRBMI) on children's educational outcomes through the Logit model, Double Selection Lasso model, and PSM. It is found that participating in URRBMI had no significant effect on children's Chinese performance, but had a significant negative effect on children's math performance. The negative effect is more obvious for children who participating in the New Cooperative Medical Scheme (NCMS). The paper also studies the channel effects of how participating in URRBMI influences children's educational outcome trough two different way. It is noticed that both channel effects are not significant, that is, participation in URRBMI neither improves children's health nor increases household education expenditures.